Experimental characterization and crystal plasticity modeling of anisotropy, tension-compression asymmetry, and texture evolution of additively manufactured Inconel 718 at room and elevated temperatures. (February 2020) - Ghorbanpour, Saeede; Alam, Md Ershadul; Ferreri, Nicholas C.; Kumar, Anil; McWilliams, Brandon A.; Vogel, Sven C.; Bicknell, Jonathan; Beyerlein, Irene J.; Knezevic, Marko
Abstract: In this work, strength and microstructural evolution of superalloy Inconel 718 (IN718) are characterized as a function of the initial microstructure created via direct metal laser melting (DMLM) additive manufacturing (AM) technology along with subsequent hot isostatic pressing (HIP) and heat treatments as well as wrought processing. Stress-strain curves are measured in tension and compression from room temperature to 550 °C and crystallographic texture is characterized using neutron diffraction. Furthermore, a recently developed crystal plasticity model incorporating the effects of precipitates is extended to interpret the temperature dependent deformation behavior of the alloy. The model accounts for solid solution, precipitate shearing, and grain size and shape contributions to initial slip resistance, which evolves with a dislocation density-based hardening law considering latent hardening, while non-Schmid effects are taken into account in the activation stress. Part of the experimental data is used for calibration of the model, while the rest is used for experimental validation of the model. It is shown that the model is capable of modeling the data with accuracy. Based on the comparison of the data and model predictions, it is inferred that the grain structure and texture give rise to plastic anisotropy of the alloy, while its tension-compression asymmetry results from non-Schmid effects and latent hardening. Highlights: Mechanical response of alloy IN718 is studied as a function of the initial microstructure created by variation in processing. The room and elevated temperature stress-strain responses are provided for the alloy. An elasto-plastic crystal plasticity model is extended to predict temperature-dependent deformation of the alloy. The model predicts hardening and texture evolution for several test directions across the studied temperature range. The model reveals that anisotropy stems from grain structure, while asymmetry from non-Schmid activation and latent hardening.